What is the current state of cloud service research and its promise for the future? A systematic literature review - Phan, Van Hung (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The information technology (IT) industry has recently witnessed the proliferation of cloud services, which have allowed IT service providers to deliver on-demand resources to customers over the Internet. This frees both service providers and consumers from traditional IT-related burdens such as capital and operating expenses and allows them to respond rapidly to new opportunities in the market. Due to the popularity and growth of cloud services, numerous researchers have conducted studies on various aspects of cloud services, both positive and negative. However, none of those studies have connected all relevant information to provide a holistic picture of the current state of cloud service research. This study aims to investigate that current situation and propose the most promising future directions. In order to determine achieve these goals, a systematic literature review was conducted on studies with a primary focus on cloud services. Based on carefully crafted inclusion criteria, 52 articles from highly credible online sources were selected for the review. To define the main focus of the review and facilitate the analysis of literature, a conceptual framework with five main factors was proposed. The selected articles were organized under the factors of the proposed framework and then synthesized using a narrative technique. The results of this systematic review indicate that the impacts of cloud services on enterprises were the factor best covered by contemporary research. Researchers were able to present valuable findings about how cloud services impact various aspects of enterprises such as governance, performance, and security. By contrast, the role of service provider sub-contractors in the cloud service market remains largely uninvestigated, as do cloud-based enterprise software and cloud-based office systems for consumers. Moreover, the results also show that researchers should pay more attention to the integration of cloud services into legacy IT systems to facilitate the adoption of cloud services by enterprise users. After the literature synthesis, the present study proposed several promising directions for cloud service research by outlining research questions for the underexplored areas of cloud services, in order to facilitate the development of cloud service markets in the future.